Coccoidea (Insecta: Hemiptera) associated with Cactaceae in Argentina - Claps, Lucia Elena (2001)
Coccoidea (Insecta: Hemiptera), commonly called “cochineal insects”, “mealybugs”or “scale insects”, show a marked sexual dimorphism and display a high degree of adaptation to the parasitic life. They have adapted to become a specialised group of small phytophagous insects no more than a few millimetres in length. This paper provides more information with regard to Coccoidea species and their hosts recorded on Argentinean cacti. Six species of Dactylopiidae: Dactylopius austrinus De Lotto, Dactylopius ceylonicus (Green), Dactylopius confertus De Lotto, Dactylopius coccus Costa, Dactylopius salmianus De Lotto, and Dactylopius zimmermanni De Lotto; four species of Diaspididae: Abgrallaspis cyanophylli Signoret, Aonidomytilus albus (Cockerell), Diaspis boisduvalli Signoret, Diaspis echinocacti (Bouché); and two species from Pseudococcidae: Hypogeococcus festerianus (Lizer y Trelles) and Hypogeococcus pungens Granara de Willink, are reviewed. The characterisation and importance of the three registered families are also provided.